NOISE MANAGEMENT IN AN AERONAUTICAL MAINTENANCE CENTER - Silva, Rafael Felipe Guatura da (2020)
Noise can damage human health, such as hearing loss, stress, irritability, sleep disorders and fatigue. In addition, it can be a facilitator for the occurrence of errors in the work environment and reduce the professional's performance. The aim of this study was to assess the impact of noise on the physical and mental performance of professionals in an aeronautical maintenance facility. Descriptive, quantitative and exploratory study used as method. Applied on a sample of pilots, aircraft mechanics, inspectors and managers at an aeronautical maintenance center a self-reported questionnaire, seeking to identify health problems and symptoms related to excessive noise in the workplace. The results obtained identify professionals who report feeling frequently irritated, experiencing headaches, difficulties with concentration, hearing tinnitus after working hours and hearing problems. The frequency of hearing problems increased according to the age of the professionals and the time they work with aeronautical activity. In view of this, the results refer to the noise pressure levels of this maintenance center that affect both the health of human resources, as well as the performance of their professional activities.